Feed Intake and Digestibility of Nutrients as Affected by Feeding of Hydroponics Maize Fodder in Rathi Cows - Limba, A. K.; Dhuria, R. K.; Sharma, T.; Nehra, R. (Indian Journal of Animal Nutrition, 2017)
Sixteen dairy Rathi cows of similar age and body weight were distributed in 4 groups of 4 animals each in order to study the effect of feeding of hydroponics maize fodder on feed intake and digestibility of nutrients. The study was conducted for 120 days. The animals in group T1 (control) were fed 4.5 kg concentrate mixture (CP 20%), 4 kg groundnut straw and wheat straw ad lib. In group T2, 75% of CP was met through concentrate mixture (3.375 kg) and rest through hydroponics maize fodder (7.0 kg) alongwith 4 kg groungnut straw and ad lib. wheat straw. While in group T3, 14 kg hydroponics maize fodder, 2.25 kg concentrate mixture and 4 kg groundnut straw were given along with ad lib. wheat straw. In group T4, the animals were fed 21 kg of hydroponics maize fodder, 1.125 kg concentrate mixture, 4 kg groundnut straw and ad lib. wheat straw. The DM intake was higher (P<0.01) in group T1 (control) in comparison to group T4. The digestibility of DM (65.27 vs. 58.69), OM (69.14 vs. 60.26), CP (71.18 vs. 62.48), CF (58.70 vs. 52.93), NFE (70.63 vs. 66.26) and ADF (47.32 vs. 42.78) were higher (P<0.05) for cows fed hydroponics maize fodder in group T4 compared to group T1 (control). Therefore, feeding of hydroponics maize fodder decreased DM intake and increased digestibility of nutrients in Rathi cows.